Photographs and the practice of history a short primer - Edwards, Elizabeth 1955- (Bloomsbury Academic, 2022)
Cover -- Contents -- Preface -- Acknowledgements -- Introduction -- 1 Inscription -- 2 Distance -- 3 Scale -- 4 Event -- 5 Presence -- 6 Context -- 7 Materiality -- 8 Digital -- Bibliographic Afterword -- Selected Reading -- List of Images -- Notes -- Index.